An Analysis of Money's Worth Ratios in Chile - Thorburn, Craig; Rocha, Roberto; Morales, Marco (World Bank, Washington, DC, 2012)
Empirical analyses of annuities markets have been limited to a few industrial countries and restricted by data limitations. Chile provides excellent conditions for research on annuities because of the depth of its market and the availability of data. The authors use an extensive dataset on individual annuities to examine econometrically a measure of market performance-money's worth ratios (MWRs)-or the ratio of the expected present value of annuity payments to the premium. The results show that annuitants in Chile have generally a good deal for their premiums, as indicated by MWRs higher than one, and also higher than those estimated for other countries. The difference between Chile and other countries is striking considering that annuities in Chile are indexed to prices. The wide range of indexed instruments in Chile, allowing providers to hedge their risks while extracting higher returns, helps explain the difference. The high degree of market competition has also contributed to this outcome. Efforts to improve market transparency through a new electronic quotation system have decreased the dispersion of MWRs. Finally, MWRs tend to decrease for contracts with longer durations, reflecting pricing for higher longevity and reinvestment risks. These results are consistent with separate research on the annuity rate, and indicate the need to ensure competition and market transparency, as well as to develop appropriate financial instruments for providers to ensure good outcomes for annuitants.